(untitled) (Bangladesh Journal of Plastic Surgery, 2013)
Normal hand function is a balance between the extrinsic-intrinsic and extensor-flexor group of musculature. Although individually the intrinsics are very small muscles, collectively they contribute about 50% of grip strength. Total 19 patents with claw deformity were corrected by 4 different techniques. 11 claws were due to high ulnar nerve palsy and 8 were due to low palsy. Result was excellent in 9 (47.36%), good in 7(36.84%), fair in 2(10.52%) and poor in 1(05.26%) patient. Zancollis Lasso was the most common procedure used for correction of claw deformity. 1(05.26%) patient developed swan neck deformity treated by FDS 4 tail procedure of low lesion group and final result was fair, another 1 (05.26%) patient developed contracture of the PIP joint. Though exact biomechanical correction of claw is complicated yet function of the hand can be improved with different techniques of tendon transfer. DOI: http://dx.doi.org/10.3329/bdjps.v3i1.15000 Bangladesh Journal of Plastic Surgery 2012, 3(1): 13-18